TAIWAN DILEMMA: A FLASHPOINT FOR THE GLOBAL PEACE (Margalla Papers, 2024)
With its multilayered complexities, Taiwan is not just a contentious issue but a potential flashpoint for war between China and the United States (US). Since 1949, Taiwan’s politics has oscillated between its unique status of UNSC’s permanent membership and veto power to its present status of de facto sovereignty. Despite losing its UN membership in 1971, Taiwan maintains a de facto sovereign status, which can lead to conflict at any moment. China, the US, and Taiwan maintain conflicting views over the future status and resolution of the Taiwan issue. Taiwanese prefer independent and separate identity. China demands Taiwan’s reunification with the mainland. The US pursues an unclear policy of whether, in case of aggression from China on Taiwan, the US would defend Taiwan or not. While there has been relative peace, China’s rapid rise, Taiwan’s preference against unification, declining US deterrence, and ongoing Sino-US major power rivalry increase the likelihood of forceful unification. The US policy of “Strategic Ambiguity”—an acknowledgement of the One-China policy and commitment to Taiwan’s defence—further exacerbates the risk of war over Taiwan. Bibliography EntryKhan, Aamir Hussain. 2024. "Taiwan Dilemma: A Flashpoint for the Global Peace." Margalla Papers 28 (1): 123-140.